Dexter : new blood [videorecording (DVD)] - Phillips, Clyde (Paramount Home Entertainment, 2022)
Set ten years after Dexter Morgan went missing in the eye of Hurricane Laura; he is now living under an assumed name in Upstate New York, Iron Lake, far from his original home in Miami.